Meningkatkan Kemampuan Berpikiri Kritis dan Kreatifitas Siswa dengan Model Problem Base Learning (PBL) pada Siswa Kelas IV Fase B di SD Negeri 12 Sungai Risap - Paskarada Gerada; Dicky Aprianto; Hedwigis Dian Permatasari (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This research aims to describe the application of the Problem Base Learning (PBL) model in improving the critical and creative thinking abilities of class IV phase B students at SD 12 Sungai Risap. As well as describing how the critical thinking skills and creativity of class IV phase B students at SD 12 Sungai Risap increased after implementing PBL. The type of research is Classroom Action Research (PTK), entitled "Improving Students' Critical Thinking Abilities and Student Creativity with the PBL Model in Class IV Phase B Students at SD Negeri 12 Sungai Risap." This research was carried out at SDN 12 Sungai Risap, Binjai Hulu District, Sintang Regency from 13 to 19 September 2024. This research was carried out using the Problem Based Learning model. The research subjects were students of class IV Phase B at SDN 12 Sungai Risap. The research object was the application of the Problem Base Learning (PBL) model in improving the critical and creative thinking abilities of class IV phase B students at SD 12 Sungai Risap. The research was carried out in two classroom actions. The activity stages include planning, implementation, observation, analysis and reflection which are carried out face to face. Data collection was carried out by making direct observations and distributing questionnaires to students. Data analysis techniques are carried out through data collection, data condensation, presentation and drawing conclusions. The research results show that the application of the Problem-Based Learning (PBL) model can improve the critical thinking skills of class IV Phase B students at SD 12 Sungai Risap. Overall, PBL forces students to be active in their learning process, thereby improving critical thinking skills by teaching them to analyze, evaluate, and make better decisions. The application of the Problem-Based Learning (PBL) model can increase the creativity of class IV Phase B students at SD 12 Sungai Risap. Use of Innovative Ideas, Diverse Learning Outcome Products, Alternative Approaches to Problem Solving, Deeper Exploration. Overall, PBL facilitates increased critical thinking and creativity in students by placing them in learning situations that require complex and innovative problem solving.